Postharvest packaging and marketing innovation adoption in Nigeria: The case of plastic crate - Yami, Mesay; Saweda, Liverpool-Tasie; Wossen, Tesfamicheal; Oyinbo, Oyakhilomen; Yamauchi, Futoshi; Chamberlin, Jordan; Feleke, Shiferaw; Abdoulaye, Tahirou (International Food Policy Research Institute, 2024)
Postharvest loss of horticultural crops is very high in most developing countries, and most of the loss occurs during production, harvesting, and transporting stages. Postharvest technologies (PHTs) are therefore important to reducing food loss and wastage and critical to both national and international food security agendas. This report provides the status quo of postharvest innovation adoption in Nigeria by taking the case of horticultural growers’ adoption of postharvest packaging and transportation innovation such as returnable plastic crates. Primary data were collected from 1704 farmers using a multistage random sampling technique. Our findings reveal low adoption of PHT, with only 8% of rainfed and 14% of irrigation farmers utilizing PHT for packaging and transporting perishable agricultural products. Growers who adopted PHT received a market price that was twice as high as those who did not, encouraging sustained adoption of PHT by growers. The results prove that the high costs and limited availability in rural areas, rather than awareness gap, discourage farmers from using PHT. The research suggests interventions to address these challenges by utilizing flexible distribution strategies, such as engaging small and micro enterprises to offer rental PHT services in rural areas.